La morfologia del vocabolario fondamentale - Kardos, Orsolya (Verbum – Analecta Neolatina, 2003)
This paper analyses the fundamental vocabulary of Italian from a morphological point of view. The goal is to provide an overview of the most diVused derivational processes and to check whether they can contribute to the enrichment of the vocabulary of language learners in a productive way. The results could be of interest for teachers as well as lexicographers.